(untitled) (Arquivos de Ciências do Mar, 2018)
In the past twenty tive years, the concept of species diversity has been much used by ecologists and it suggests something more than the notion of the effective number of species present in a sample (Lioyd et al., 1968; Hill, 1973). A community (or collection) in which ali the individuais belong to one species has no diversity, while one in which every individual belongs to a different species has the maxi.mum possible diversity (Pielou, 1966a). This can be thought as something analogous to statistical variance. In the same way that a variance provides a measurement of the variability of some quantitative variable, a diversity index measures the variability of the species identity.